HUBUNGAN FAKTOR PERILAKU DENGAN KERUGIAN EKONOMI (ECONOMIC LOSS) PENDERITA DIABETES MELITUS TIPE 2 - Muhammad Ali Makaminan (POLTEKKES KEMENKES MANADO, 2014)
Diabetes mellitus type 2 or Non Insulin Dependent Diabetes Mellitus (NIDDM) is a metabolicdisease caused by a progressive disorder of insulin secretion and insulin resistance. Thepurpose of researchis to analyze the correlation between the behavior of economic loss(Economic Loss) on Endocrine Polyclinic Hospital. Prof. Dr.R.D.Kandou Manado in 2013. Thisresearch isquantitative research design Cross-sectional study. The research was conducted twomount in the department clinical’s Endokrine of Prof Dr.R.D. Kandou Manado Hospital with 239people sampled purposively selected. Collecting data using questionnaires. Data was analyzedusing univariate, bivariate and multivariate analyzes.The results showed thatthere was norelationship between knowledge (p =0.391), attitude to diet (p=0.524) with economic losses(Economic Loss), andthere is a relationship between adherence to the diet (p=0.002) andinterest in physical activity (p=0.007) with economic losses.